Optimalisasi Rantai Pasok Bahan Baku untuk Meningkatkan Keberlanjutan Produksi pada UMKM Industri Pangan: A Systematic Literature Review - Zaskya Chaira Amantayeva; Faldha Ajazul Sururin; Rozatul Jannah; Zunia Luwinsky Farikhah; Putri Esa Rahmawati; Aisyah Elysia Zerlina; Lifa Farida Panduwinata; Adi Pratama Sanjaya (Jurnal Logic: Logistics & Supply Chain Center, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the food industry play a vital role in the national economy, but their production sustainability still faces various challenges, particularly in managing the raw material supply chain. This study aims to identify key challenges in the raw material supply chain, analyze the optimization strategies implemented, and assess their impact on production sustainability in MSMEs in the food industry. The study used the Systematic Literature Review (SLR) method with the stages of identification, selection, quality assessment, and synthesis of articles obtained through Google Scholar. Based on the inclusion and exclusion criteria, and quality assessment, eight articles were obtained that met the requirements for analysis. The results showed that the main challenges include supply uncertainty, price fluctuations, inconsistent raw material quality, limited inventory control, and dependence on certain suppliers. Optimization strategies that are widely applied include the implementation of Supply Chain Management (SCM), the Economic Order Quantity (EOQ) method, Safety Stock, Reorder Point (ROP), First in First Out (FIFO), strengthening supplier relationships, and risk management. The implementation of these strategies can improve operational efficiency, maintain raw material availability, reduce the risk of production disruptions, minimize waste, and support the sustainability of MSME production in the food industry.